Prioritizing Strategies to Improve University Students' Reading Interest: An Integrated SWOT–Analytical Hierarchy Process Approach - Suprianto Suprianto; Muslimin Muslimin; Andi Onasis (Journal of Educational Development and Learning (JEDAL), 2026)
University students' reading interest remains a significant challenge in higher education despite the widespread availability of libraries, digital resources, and internet access. Low intrinsic motivation, assignment-oriented reading habits, and increasing digital distractions have limited the development of a sustainable academic reading culture. Therefore, identifying strategic priorities that effectively improve students' reading interest has become increasingly important for universities. This study aims to formulate and prioritize strategies for improving university students' reading interest by integrating the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis with the Analytical Hierarchy Process (AHP). A qualitative descriptive approach was employed. Data were collected through semi-structured interviews with seven purposively selected student informants to identify internal and external factors affecting reading interest. Subsequently, SWOT analysis was used to formulate strategic alternatives, while expert judgment from lecturers was utilized in the AHP pairwise comparison to determine strategy priorities. The findings indicate that students' reading interest is influenced by both internal and external factors. Internal strengths include the availability of university libraries, internet access, lecturer support, and digital academic resources, whereas the major weaknesses are low intrinsic motivation and reading practices that are primarily driven by academic assignments. Externally, digital technology provides opportunities to strengthen literacy programs but also presents challenges through social media and digital entertainment. The SWOT analysis generated eight strategic alternatives, and the AHP prioritization identified the Extensive Reading Program as the highest-priority strategy, followed by the Campus Reading Culture Program, Gamified Reading Challenge, Reading Strategy Instruction, Critical Reading Skills Training, Reading Mentorship Program, Digital Reading Platform Optimization, and the Collaborative Literacy Community. The novelty of this study lies in integrating SWOT and AHP to develop a systematic decision-making framework for prioritizing strategies to improve university students' reading interest. Unlike previous studies that primarily identify factors influencing reading behavior, this research provides evidence-based strategic priorities that can support literacy policy development and implementation in higher education institutions.